Map of the vulnerabiliy to pollution of the Apuo-Versilia aquifer (Tuscany - Italy) - Pranzini, Giovanni; Di Martino, Francesco; Fanti, Riccardo; Fontanelli, Katia (Acque Sotterranee - Italian Journal of Groundwater, 2019)
The authors have drawn up the Map of Vulnerability to Pollution for groundwater of the Apuo-Versilia coastal Plain using the SINTACS method. The availability of a large number of subsoil data (stratigraphic columns and piezometric surveys) integrated in a GIS environment, has allowed to obtaining a large detail map on an extended area (about 152 Km2). Vulnerability rates from high to very high prevail in much part of the Plain; this poses a risk for groundwater, which represent an important resource for civil water supply.